An integrated immunoinformatic approach to design a novel multiepitope chimeric vaccine against Mycoplasma phocimorsus as a causal agent of bloodstream infections - Yu, Rongrong; Hasan, Ahmad; Ibrahim, Muhammad; Alonazi, Wadi B.; Bin, Li (Frontiers in Immunology, 2025)
IntroductionMycoplasma phocimorsus is increasingly recognized as an emerging human pathogen, despite its primary association with marine mammals. It has recently been identified as a causative agent of bloodstream infections and sepsis, a major cause of mortality among hospitalized patients. To date, no approved vaccine is available against M. phocimorsus, underscoring the urgent need for preventive strategies.MethodsThe current study was aimed at employing immunoinformatic approaches to design a vaccine based on multiple epitopes derived from the six core proteomic datasets of representative M. phocimorsus strains.ResultsBy subtractive genomics, we retrieved 3,576 nonredundant proteins from M. phocimorsus proteomes following only one putative immunoglobulin-blocking virulence outer membrane protein conserved in six strains. The epitopes derived from the putative immunoglobulin-blocking virulence protein exhibited promising features such as strong binding affinity, lack of allergenicity, nontoxic properties, high antigenicity scores, and excellent solubility. Moreover, these epitopes include nine linear B cell epitopes, eight MHC class I epitopes, and five MHC class II epitopes. In addition, adjuvants and linker molecules were successfully merged into a chimeric vaccine with significant immunogenicity and stimulation of both adaptive and innate immune responses. The promising potential of the selected vaccine candidates was further validated through their favorable physico-chemical characteristics, strong interaction with TLR-4, and stable performance in molecular dynamics simulations.DiscussionThese results suggest that the putative immunoglobulin-blocking outer membrane virulence protein could effectively participate in activating the primary innate immune response, thereby serving as a strong foundation for subsequent adaptive immune activation. The proposed vaccine provides substantial basis for developing effective preventive and therapeutic measures against the zoonotic M. phocimorsus, whose association with sepsis, soft tissue, and respiratory infections, particularly in immunocompromised individuals emphasizes the crucial need for vaccine development.